Prinsip-prinsip Dasar Al-Qur’an tentang Perilaku Konsumsi - Syaparuddin Syaparuddin (Universitas Islam Negeri Mataram, 2011)
This paper aims to uncover some basic tenets of how muslim’s consumerism should be as stated in al-A‘râf (7):31 and al-Baqarah (2):168. Those basic principles are spending income proportionally, caring for others’ needs, consuming a good and lawful goods or service, and having a simple life Although the definition of consumption, generally, is enjoying goods and services to fulfill human’s needs, moslem can not deliberately do it without considering those principles. The ultimate goal of muslim is not only current and on going proseperity but also future and hereafters’